Immediate results of aortic valve reconstruction using Ozaki method - В.М. Todurov; I.Yu. Mokryk; I.O. Aksionova; N.V. Ponych; C.M. Monastyrska; О.А. Yepanchintseva; I.M. Kuzmich; V.B. Demianchuk (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the immediate results of reconstruction of the aortic valve using Ozaki method, to analyze the most important aspects of perioperative management of these patients. Materials and methods. In the period from December 2016 till August 2017 at Heart Institute of Healthcare Ministry of Ukraine 40 patients underwent Ozaki Procedure. There were 21 males (51.2 %). Mean age was 66 ± 11 years. 14 (35 %) patients had bicuspid aortic valve. Preoperative examination demonstrated aortic valve average peak pressure gradient of 93.7 ± 27.5 mm Hg; aortic annular diameter was 22.7 ± 3.1 mm. Surgical technique is based on replacement of every single cusp of the diseased valve with neocusp trimmed using original Ozaki set from patients own pericardium treated with glutaraldehyde. Results. Ozaki procedure was successfully performed in every patient. There were no mortality or major complications in postoperative period. Aortic regurgitation was absent, trivial or mild in all cases. Average peak pressure gradient at discharge from the hospital was 14.5 ± 2.3 mm Hg. Conclusions. Ozaki procedure is a contemporary method of bioprosthesis of aortic valve. Immediate results of Ozaki procedure are promising. This permits to use Ozaki procedure in accordance to the clinical guidelines for biologic prostheses of aortic valve. This method is especially valuable in patients with small aortic root, as it permits to eliminate a surgical problem of patient-prosthesis mismatch. Randomized trial is needed to verify advantages and limitations of this method compared to standard techniques at long-term follow-up.